Untitled

unknown
plain_text
a year ago
2.6 kB
1
Indexable
Never
```{PROPOSAL 2,pressure of CFWH from reheat pressure, 3FWH}

p_b=150 [bar]

T_max= 500 [c]

p_reheat=30.5 [bar]

T_reheat= 500 [c]

p_c = 0.1 [bar]

p_OFWH=5.83[bar]

p_FIRSTCFWH=1.268[bar]

p_SECONDCFWH=30.5[bar]

eta_turbine=0.85

eta_pump=0.95

z=0.0139

y=0.165

{point 1}

p[1]=p_c

x[1]=0

h[1]=enthalpy(water,p=p[1],x=x[1])

s[1]=entropy(water,p=p[1],x=x[1])

{point 2}

p[2]=p_OFWH

{isentropic}

s_s[2]=s[1]

h_s[2]=enthalpy(water,p=p[2],s=s_s[2])

{Actual}

h[2]=((h_s[2]-h[1])/eta_pump)+h[1]

{point 3}

p[3]=p_OFWH
T[3]=T[13]
{h[3]=4.18*T[3]}

{point 4}

p[4]=p_OFWH

x[4]=0

h[4]=enthalpy(water,p=p[4],x=x[4])

s[4]=entropy(water,p=p[4],x=x[4])

{point 5}

p[5]=p_b

s_s[5]=s[4]

h_s[5]=enthalpy(water,p=p[5],s=s_s[5])

{Actual}

h[5]=((h_s[5]-h[4])/eta_pump)+h[4]

{point 6}

p[6] =p_b
T[6]=T[15]
{h[6]=enthalpy(water,p=p[6],T=T[6])}
{h[6]=4.18*T[6]}

{point 7}

p[7] =p_b

T[7]=T_max

h[7]=enthalpy(water,p=p[7],T=T[7])

s[7]=entropy(water,p=p[7],T=T[7])

{point 8}

p[8]=p_reheat

s_s[8]=s[7]

h_s[8]=enthalpy(water,p=p[8],s=s_s[8])

{Actual}

h[8]=h[7]-((h[7]-h_s[8])*eta_turbine)

{point 9}

p[9] =p_reheat

T[9]=T_max

h[9]=enthalpy(water,p=p[9],T=T[9])

s[9]=entropy(water,p=p[9],T=T[9])

{point 10}

p[10] =p_OFWH

s_s[10]=s[9]

h_s[10]=enthalpy(water,p=p[10],s=s_s[10])

{Actual}

h[10]=h[9]-((h[9]-h_s[10])*eta_turbine)

s[10]=entropy(water,p=p[10],h=h[10])

{point 11}

p[11] =p_FIRSTCFWH

s_s[11]=s[10]

h_s[11]=enthalpy(water,p=p[11],s=s_s[11])

{Actual}

h[11]=h[10]-((h[10]-h_s[11])*eta_turbine)

s[11]=entropy(water,p=p[11],h=h[11])

{point 12}

p[12] =p_c

s_s[12]=s[11]

h_s[12]=enthalpy(water,p=p[12],s=s_s[12])

{Actual}

h[12]=h[11]-((h[11]-h_s[12])*eta_turbine)

s[12]=entropy(water,p=p[12],h=h[12])

{point 13}

p[13]= p_FIRSTCFWH
x[13]=0
h[13]=enthalpy(water,p=p[13],x=x[13])
T[13]=TEMPERATURE(Water,h=h[13],p=p[13])

{point 14}

h[14]=h[13]

{point 15}

p[15]= p_reheat
x[15]=0
h[15]=enthalpy(water,p=p[15],x=x[15])
T[15]=TEMPERATURE(Water,h=h[15],p=p[15])

{point 16}

h[16]=h[15]

{mass balance of SECONDCFWH}

(h[8])*(x)+(h[5])=(h[6])+(x)*(h[15])

{mass balance of FIRSTCFWH}

(z)*(h[11])+(1-x-y)*(h[2])=(h[13])*(z)+(h[3])*(1-x-y)

{mass balance of OFWH}

(h[10])*(y)+(h[3])*(1-x-y)+(h[16])*(x)=h[4]